1980
DOI: 10.1080/00222216.1980.11969447
|View full text |Cite
|
Sign up to set email alerts
|

Wilderness Recreation Experiences: The Rawah Case

Abstract: This research focused on defining wilderness recreation experiences in terms o f the psychological outcomes sought by the recreational users o f the Rawah Wilderness in Colorado. Information on the outcomes was used to type users so that groups seeking different experiences could be identified. From a sample o f 264 people, there were five types o f wilderness recreation experiences identified. Use o f information on the psychological outcomes sought b y recreationists and on the types o f recreationists pursu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…Their major reported motivations to visit Starkey Hill were "to enjoy nature" (95.1%), "for physical exercise" (91.5%), "to escape the pressures of everyday life" (65.9%), "to socialize with friends and family" (59.8%), "for solitude and tranquility" (59.8%) and "for personal reflection" (53.7%). These reported motivations are supported by past motivational research on recreational uses who participate in activities in natural areas (Walker et al, 1998;Ribe, 1994;Virden and Knopf, 1989;Brown and Haas, 1980).…”
Section: Visitor Profilementioning
confidence: 51%
See 2 more Smart Citations
“…Their major reported motivations to visit Starkey Hill were "to enjoy nature" (95.1%), "for physical exercise" (91.5%), "to escape the pressures of everyday life" (65.9%), "to socialize with friends and family" (59.8%), "for solitude and tranquility" (59.8%) and "for personal reflection" (53.7%). These reported motivations are supported by past motivational research on recreational uses who participate in activities in natural areas (Walker et al, 1998;Ribe, 1994;Virden and Knopf, 1989;Brown and Haas, 1980).…”
Section: Visitor Profilementioning
confidence: 51%
“…Managers can facilitate the ability of users to realize their desired experiences by ensuring that the settings that contribute greatly to their experiences are made available (Manfredo et al, 1983;Brown and Haas, 1980). This study identified specific setting attributes and experience preferences of users by assessing the effect of recreational use impacts on hiking experiences in natural areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the purpose of the current study is to examine whether wilderness users' attitudes toward management actions (e.g. restrictions on use) vary depending on their motives for visiting the national parks and wildernesses, as proposed by some previous research (Brown & Haas 1980, Virden & Schreyer 1988, Shultis 1999. Our empirical data come from a sample of visitors to DovrefjellSunndalsfjella National Park in southern Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Wilderness visitors generally believe that the attributes described in these three core themes define wilderness (Brown and Haas 1980, Hall 2001, Kaye 2000, Kendra and Hall 2000. However, the complexity of human experiences suggests that many factors contribute in known and unknown ways to the experience of solitude or primitive and unconfined recreation.…”
Section: "Outstanding Opportunities For Solitude or A Primitive And Umentioning
confidence: 99%